WILLIAM SHAKESPEARE’S LEGACY IN 21 CENTURY - Majitova Feruza Gayrat qizi; Xamitov Eldorbek Erkin o`g`li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
This article examines William Shakespeare’s legacy and works or writings in 21 century. In addition, this article explores how Shakespeare’s writing has influenced and continues to inspire modern authors.